Evaluation of the ways of coping with stress and the personality traits in women exposed to violence: A comparative study - Barut, Sumeyye; Guney, Esra; Ucar, Tuba (Wiley, 2022)
Purpose To determine the stress-coping methods and personality traits of the women who were exposed to violence. Design and Methods This cross-sectional study was conducted by using a web-based online survey with 1242 women in Turkey. Findings Women who were exposed to violence used mostly emotional strategies in coping with stress. The women's personality traits did not affect whether they were victims of the violence. Practice Implications It is necessary to take initiatives to encourage the use of effective methods in coping with stress. Other studies should be conducted to determine the personality traits of women exposed to violence.
Keywords: coping with stress; domestic violence; personality traits; violence against women; women